1999
DOI: 10.1046/j.1365-3016.1999.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and respiratory illness of children in São Paulo, Brazil

Abstract: This investigation reports the association between air pollution and paediatric respiratory emergency visits in São Paulo, Brazil, the largest city in South America. Daily records of emergency visits were obtained from the Children's Institute of the University of São Paulo for the period from May 1991 to April 1993. Visits were classified as respiratory and non-respiratory causes. Respiratory visits were further divided into three categories: upper respiratory illness, lower respiratory illness and wheezing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
70
2
38

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 30 publications
11
70
2
38
Order By: Relevance
“…The magnitude of association found between the air pollutant studied and pneumonia admission rates was similar to that found in other studies 4,5,9 in São Paulo. This is an expected finding since both cities have just about the same sources of pollutants, i.e., especially moving sources as well as fixed sources (plants), thus producing similar toxic effects.…”
Section: Time-series Studies Have Showed An Associationsupporting
confidence: 89%
See 3 more Smart Citations
“…The magnitude of association found between the air pollutant studied and pneumonia admission rates was similar to that found in other studies 4,5,9 in São Paulo. This is an expected finding since both cities have just about the same sources of pollutants, i.e., especially moving sources as well as fixed sources (plants), thus producing similar toxic effects.…”
Section: Time-series Studies Have Showed An Associationsupporting
confidence: 89%
“…4,5,9 However, in the present study, which was conducted out of a metropolitan center, air pollutants showed to have seasonal distribution and their average levels were below those found by Braga et al 4 in the city of São Paulo in the early 1990's.…”
Section: Time-series Studies Have Showed An Associationcontrasting
confidence: 77%
See 2 more Smart Citations
“…The association between air pollution and human health in the city of São Paulo, Brazil, has long been of public concern and the subject of several studies (Saldiva et al, 1994;Saldiva et al, 1995;Miraglia et al, 1997;Pereira et al, 1998;Braga et al, 1999;Lin et al, 1999 ). The main objective of the present investigation is to examine the relationship between air pollution and mortality, controlling for meteorological variables, based on daily death counts for people over 65 years old in São Paulo.…”
Section: Introductionmentioning
confidence: 94%